Clinical Experience of the Klippel-Trenaunay Syndrome - Sung, Hyung Min; Chung, Ho Yun; Lee, Seok Jong; Lee, Jong Min; Huh, Seung; Lee, Jeong Woo; Choi, Kang Young; Yang, Jung Dug; Cho, Byung Chae (Archives of Plastic Surgery, 2015)
Background The Klippel-Trenaunay syndrome (KTS) is characterized by three clinical features, namely cutaneous capillary malformations, venous malformations, and soft tissue and/or bony hypertrophy of the extremities. The varied manifestations are attributed to the unpredictable clinical nature and prognosis of the syndrome. To elucidate the clinical characteristics of this disease, we reviewed a relatively large number of KTS patients who presented to our vascular anomalies center.Methods We conducted a retrospective study with 19 patients who were diagnosed with KTS and treated in our vascular anomalies clinic between 2003 and 2014, and examined their demographic characteristics, their clinical features, and the treatments administered.Results The sex distribution was balanced, with 9 (47%) males and 10 (53%) females. The mean follow-up period was 4.1 years (range, 7 months-9 years). Most of the patients received conservative treatments such as medication or physiotherapy. Compression therapies such as wearing of elastic garments/bandages were also administered, and surgical interventions were considered only when the patients became excessively symptomatic. Other treatments included laser therapy and sclerotherapy, and all the treatments were adjusted according to each case, tailored to the conditions of the individual patients.Conclusions KTS is an extremely rare, multifactorial disorder that induces widely varied symptoms. Because of this unique feature, plastic surgeons, when not careful, tend to attach a one-sided importance to typical symptoms such as limb hypertrophy or capillary malformation and thus overlook other symptoms and clinical features. KTS can be suspected in all infants who show capillary malformations or limb hypertrophy and require a multi-disciplinary approach for comprehensive management.
Keywords: Klippel-Trenaunay-Weber syndrome; Vascular malformations; Capillary malformations